A comparative study between D2Q9 and D2Q5 lattice Boltzmann scheme for mass transport phenomena in porous media. (1st November 2019) - Espinoza-Andaluz, Mayken; Moyón, Ayrton; Andersson, Martin
Abstract: Characterization of different transport phenomena through porous media represents a key factor to improve mechanical or electrical properties of materials. Porous materials have several applications in different fields such as geological sciences, energy sciences or biological applications. Considering the difficulty to carry out experimental studies in porous media, these transport phenomena are more feasible to describe with computational tools, i.e., to compute the involved parameters. In this scenario, the Lattice Boltzmann Method (LBM) appears as a powerful tool to solve different transport phenomena at micro- and meso-scale. The fluid flow behavior, analyzed with LBM, is commonly solved using the D2Q9 scheme. This scheme has shown a reliable solution for fluid flow problems. On the other hand, the mass transport phenomena are recommended to be solved using the D2Q5 scheme. However, there is not yet a comparative, detailed and complete study of the impact of using such schemes in porous media. The purpose of this study is to analyze the impact of using the D2Q5 and D2Q9 LBM scheme in the computation of mass concentration within porous media considering a constant particle size. Parameters such as porosity and tortuosity are also considered in this study.